Research into Bills of Quantities (BQ): where can it be focused? - Bandi, Shamsul Hadi; Abdullah, Fadhlin (Royal Institutions of Surveyors Malaysia, 2015)
There are concerns reported on the uses of the Bills of Quantities (BQ). This has called for a review to be conducted with an aim to suggest a gap for further research to be steered in the area. Accordingly, the objectives of this paper are: (1) to critically review the literatures in order to identify the issues on the application of the BQ in the construction industry, and (2) to synthesise the outcome of the review process in order to identify relevant research focus. The study which had essentially employed an extensive literature review had synthesised three categories of issues related to: (1) information; (2) format; and (3) working methods. Solutions were identified to focus on improving the BQ format alone hence not entirely parallel with the categories of issues synthesised from the literature. This represents the gap that need to be expedited further through research. For this reason, this paper had suggested that research should be focused at determining the BQ information contents and the issues impeding the uses of the BQ. Research into this aspect is expected to contribute by offering substantial improvement to the uses of the BQ and is of significant value in identifying the gap in the previous researches.